Development of a charitable decentralised autonomous organisation (DAO) and setting up reporting processes - Balogh, Karel; Bruckner, Tomáš, 1974-; Potančok, Martin; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2023)
Charitable decentralized autonomous organizations (DAOs) have emerged as a promising alternative approach to philanthropy. This thesis investigates the po- tential of charitable DAOs as an alternative to traditional charities, focusing on the technical, governance, and practical aspects of developing and implementing a DAO model tailored to the specific needs of the charity sector. The ultimate goal is to create a more transparent, accountable, and efficient philanthropic land- scape. The methodology employed in this research includes a literature review and short case studies to build a foundational understanding of DAOs and their relevance within the nonprofit sector associated with charitable organizations. Additionally, the research involves the development of a prototype DAO to prac- tically demonstrate the implementation and functioning of the proposed model. The conclusion summarizes the primary findings and contributions of the re- search, discusses limitations and future research directions, and provides implementation recommendations for the DAO as well as the reporting process.
Vedoucí práce: Tomáš Bruckner
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: business intelligence [obor dipl. práce]; diplomové práce; master's theses